Polymorphisms in mTOR and Calcineurin Signaling Pathways Are Associated With Long-Term Clinical Outcomes in Kidney Transplant Recipients - Campos-Salazar, Antony Brayan; Genvigir, Fabiana Dalla Vecchia; Felipe, Claudia Rosso; Tedesco-Silva, Helio; Medina-Pestana, José; Monteiro, Gabriela Vieira; Basso, Rodrigo de Gouveia; Cerda, Alvaro; Hirata, Mario Hiroyuki; Hirata, Rosario Dominguez Crespo (Frontiers in Pharmacology, 2018)
Monitoring of immunosuppressive drugs, such as calcineurin and mTOR inhibitors, is essential to avoid undesirable kidney transplant outcomes. Polymorphisms in pharmacokinetics-related genes have been associated with variability in blood levels of immunosuppressive drugs and adverse effects, but influence of pharmacodynamics-related genes remains to be elucidated. The influence of polymorphisms in genes of the mTOR and calcineurin signaling pathways on long-term clinical outcomes was investigated in Brazilian kidney transplant recipients within the one-year post-transplant. Two-hundred sixty-nine kidney transplant recipients were enrolled at a kidney transplant center in Sao Paulo city, Brazil, and treated with tacrolimus plus everolimus or mycophenolate sodium (clinical trial NCT01354301). Clinical and laboratory data, including renal function parameters and drug blood levels were recorded. Genomic DNA was extracted from blood samples. Polymorphisms in MTOR rs1057079 (c.4731G>A), rs1135172 (c.1437T>C), and rs1064261 (c.2997C>T); PPP3CA rs3730251 (c.249G>A); FKBP1A rs6033557 (n.259+24936T>C); FBKP2 rs2159370 (c.-2110G>T); and FOXP3 rs3761548 (c.-23+2882A>C) and rs2232365 (c.-22-902A>G) were analyzed by real-time PCR. Frequencies of gene polymorphisms did not differ among the treatment groups. Analysis of primary outcomes showed that patients carrying MTOR c.1437CC and FOXP3 c.-23+2882CC genotypes had higher serum creatinine than non-carriers (p<0.05) at one-year post-transplant. MTOR c.4731G allele (AG+GG genotype) was associated with increased risk for acute rejection (OR= 3.53, 95%CI=1.09-11.48, p=0.037). Moreover, one-year cumulative incidence of rejection was higher in MTOR c.4731G allele carriers compared to AA genotype carriers (p=0.027). Individually, analysis of secondary outcomes revealed that FKBP2 c.-2110GG genotype carriers had higher risk of leukopenia, FKBP1A n.259+24936C allele carriers had increased risk of constipation, and FOXP3 c.-22-902A or c.-23+2882A allele had higher risk of gastrointestinal disorders (p<0.05). However, these results were not maintained in the multivariable analysis after p-value adjustment. In conclusion, variants in genes of mTOR and calcineurin pathways are associated with long-term impaired renal function, increased risk of acute rejection, and, individually, with adverse events in Brazilian kidney transplant recipients.